SOSIALISASI PENINGKATAN KOMPETENSI DAN KETENTUAN MANAJEMEN RISIKO BAGI PENGAWAS DAN AUDITOR INTERNAL KEMENTERIAN KOPERASI DAN UKM - Purnomo, Hadi; Albart, Nicko; Listiorini, Dewi (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2023)
The implementation of training and socialization on risk management, as per Minister of Cooperatives and Small and Medium Enterprises Regulation No. 09 of 2020, aims to enhance the competence of Senior Supervisors and Internal Auditors in relation to their core duties and functions in cooperative supervision. It also aims to familiarize officials responsible for cooperative development and functional supervisors with guidelines for conducting cooperative supervision and inspections within the Ministry of Cooperatives and Small and Medium Enterprises (Kemenkop UKM). This initiative was conducted by the Community Service Team of STIMA IMMI Jakarta and Paramadina University Jakarta in collaboration with the Internal Supervisory and Auditor Unit of the Ministry of Cooperatives and SMEs. The purpose of the training and socialization program is to elevate competence, skills, knowledge, and attitudes to anticipate the increasing incidence of fraud cases in cooperatives due to the weak implementation of supervision and audits by the Ministry of Cooperatives and SMEs. The issue of fraud in cooperatives throughout Indonesia has reached hundreds of trillions of rupiah. Training and socialization, conducted using the active learning method, have had a positive impact on participants, as evidenced by the enthusiasm of participants in engaging in discussions and group activities, as well as the smooth execution of the program and its alignment with the participants' needs. Quantitatively, the PKM program has successfully improved the participants' abilities, as demonstrated by the increase in the average pre-test score from 67.4 to 75.8 during the post-test.